Women granted a pension by the Junta para la Ampliación de Estudios in Pedagogy (1907-1940). The case of Castile and Leon (Tempo e Argumento, 2021)
The “Junta para la Ampliación de Estudios” (JAE) was an institution created in 1907 with the aim of opening the frontiers of knowledge in Spain. Through its pension system, professionals from many disciplines traveled abroad to learn about the main theories and currents in their fields of study. The present work aims to deepen the knowledge of the women in the pedagogical field who were granted scholarships by the Junta from Castile and Leon between 1907 and 1940 and to analyze the incidence of the trips made in their trajectories after the rebellion produced in Spain in 1936. The study is based on the historical-educational method and makes use of the files of these professionals available in the JAE archive (Madrid), the purification files housed in the General Administration Archive, as well as the professional files recovered in provincial archives, documents triangulated with other legal sources. In order to analyse them, we have first classified the pensioners according to their posts and, later, according to whether they were penalised in the purging processes initiated during the Civil War or not. The conclusions reveal that the professionals who were committed to the renovation movement at the beginning of the 20th century –and especially to the republican educational project– suffered the harshest consequences of the purge process